(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This paper describes a study that approaches power relations expressed through deontic modal verbs in the novel The Breadwinner from a linguistic perspective focusing on the lexical-grammatical level. The study also explores, from a socio-discursive approach, the implication of habitus as a regulating principle of the social practices that permeate language and are reproduced through translation. The study allowed associating the meanings of deontic modal verbs with the forces with which power relations are constructed in this novel, in addition to identifying their various nuances, as a basis for making decisions for subsequent translation and for encouraging discussion and critical reflection on these issues.